Pengaruh Disiplin Belajar Terhadap Hasil Belajar IPS Siswa Sekolah Dasar - Habibi Habibi; A. Gafar Hidayat; Amrin Amrin (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
The purpose of this study is to determine and describe quantitative data on the effect of learning discipline on social studies learning outcomes in grade V. This study uses a quantitative approach with a Pre-Experimental Design type of research. The experimental design used is One-Group Pretest-Posttest Design. The population and sample in this study were grade V students with a total of 20 students. The data collection techniques used were observation and testing. The data analysis techniques used were descriptive statistical analysis and inferential statistical analysis. The results of this study indicate that the application of learning discipline has an effect on student learning outcomes. This can be seen in the difference in the average number of learning outcomes before applying learning discipline (pretest) of only 54.37. While the average number of learning outcomes after applying discipline (posttest) was 83.43. And the results of the inferential statistical analysis using the t test showed that the t-count value obtained was 7.935. Degrees of freedom (db) = 20 - 1 = 19 with a significance level of 0.05 obtained t table = 2.093. So, tcount > ttable or 7.935 > 2.093, then the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. This means that the application of learning discipline has an effect on student learning outcomes in the subject of social studies class V SDN Wadukopa.